Peg and Rose solve a murder - Berenson, Laurien (Berenson, Laurien. Senior sleuths mystery, 2022)
"Rose Donovan looks for the good in everyone. With her sister-in-law, Peg, that sometimes requires a lot of searching ... But after forty years of bickering, they're attempting to start over, partnering up to join the local bridge club. Peg and Rose barely have a chance to celebrate their first win before one of the club's most accomplished players is killed in his home. As the newest members, the sisters-in-law ... decide to start some digging of their own"--